Conceptualization of Theoretical Ideas on Religious Security in the Context of Western Studies of Interaction Between Society and Religion - Artem V. Zhukov; Marina B. Liga; Elena Yu. Zakharova (Гуманитарный вектор)
The article analyzes the problems of religious security presented in modern research concepts. The article is aimed at proving the idea that in Western science the problems of religious security are conceptualized within the framework of discussing the contradiction between concepts asserting the spiritual essence of religious extremism and concepts proving the social nature of threats emanating from religious associations. The theoretical basis of the presented work is the theory of structural realism. The methodological basis of the research is a systematic approach that reveals the structure of religious security as a state of protection of religious systems and values of society. The scientific novelty of the study is the fact which reveals that in Western security studies, the contradiction between the concept asserting the spiritual essence of religious threats and the concept proving the social nature of threats emanating from religious associations is essential. In conclusion, the authors state that in Western social philosophy, despite the fact that the concept of “religious threat” was practically not used, the phenomenon associated with it was discussed from various points of view. As a result of this discussion, it was attributed to a number of concepts related to the theories of religious conflict, within which it began to be evaluated as a label that was used in the process of combating confessional opponents by those who presented themselves as representatives of a “genuine” tradition and defenders of social foundations and values. The scientific and theoretical significance of the work lies in enriching the concept of structural realism with the idea of the need to distinguish between extremism as a violent act and religious doctrines as the value content of religion. The practical significance of the work lies in the fact that its results can be used in the implementation of policies aimed at preventing interaction between secular and confessional institutions and the state.